Structure-guided peptide engineering of a positive allosteric modulator targeting the outer pore of TRPV1 for long-lasting analgesia - Heng Zhang; Jia-Jia Lin; Ya-Kai Xie; Xiu-Zu Song; Jia-Yi Sun; Bei-Lei Zhang; Yun-Kun Qi; Zhen-Zhong Xu; Fan Yang (Nature Communications, 2023)
TRPV1 as a drug target suffers from side effects of hypothermia. Here, authors engineer a peptide, sRhTx, as a positive allosteric modulator of TRPV1 channel. It potentiates the activity of TRPV1 to reversibly ablate pain-sensing nerve terminals for long-lasting analgesia without changing mice body temperature.